Determination of Antioxidant Activity of Wine Byproducts and Its Correlation with Polyphenolic Content - Alonso, Ángeles M; Guillén, Dominico A; Barroso, Carmelo G; Puertas, Belén; García, Alberto (Journal of agricultural and food chemistry, 2002)
It has been demonstrated that wine and other products derived from the grape have a high antioxidant capability; as a possible consequence of this, they may have potential benefits for health. The byproducts of the winemaking process represent a source of antioxidant compounds that has been relatively unexploited to date, but that is now the subject of increasing industrial interest. This article describes an approach to the study of the antioxidant activity of grape marcs, stalks, and dregs of both white and red varieties. This activity is compared with the measurements of their content of total polyphenols and of individual polyphenolic compounds, identified and quantified by HPLC. From the results we have been able to establish a positive correlation between the antioxidant activity and the total polyphenolic content of samples, but not with specific compounds. Keywords: Antioxidant activity; wine byproducts; electrochemical method; polyphenols